THE ISSUES OF SPIRITUAL AND IDEOLOGICAL THREATS AND THEIR ELIMINATION IN THE HISTORY OF EASTERN SOCIO-PHILOSOPHICAL THOUGHT - Karimova Saida Maxamadkodirovna (Web of Journals Publishing, 2026)
This article examines the harmful consequences of the increasingly intensifying ideological threats that reflect the transformations occurring in today’s global ideological landscape. It highlights the importance of timely recognizing internal and external threats that pose real dangers to society and the state, as well as effectively utilizing the intellectual and spiritual heritage of our ancestors in ensuring ideological security.
Keywords: Threat, spiritual threat, ideological threat, danger, ignorance, negligence, vigilance, solidarity, enlightenment.